ANALISA PENINGKATAN KUALITAS CITRA BAWAH AIR BERBASIS KOREKSI GAMMA dan HISTOGRAM EQUALIZATION - Aria Hendrawan; Pulung Nurtantio Andono; Susanto Susanto (Jurnal Transformatika, 2016)
Underwater image of water quality in the dark, it depends on the depth of water at the time of image acquisition or image. The results of the image quality is adversely affecting the results matching the image pairs underwater with SIFT algorithm. This research aims to use the method of image preprocessing and Histogram Equalization Gamma Correction that works to improve the quality of images underwater. The results showed 27.76% increase using image preprocessing Gamma Correction and Histogram Equalization compared with no increase in image quality. Results of paired t-test has the null hypothesis is rejected so that there is a significant difference between the application of Gamma Correction Histogram Equalization with and without image enhancement.